Looking beyond research in doctoral education. Issue 3 (1st April 2005) - Campbell, Steven P.; Fuller, Angela K.; Patrick, David AG
Abstract : Doctoral education in the natural sciences has traditionally focused on training students as researchers. However, this is no longer sufficient to provide students with the range of skills needed to succeed in academic and non‐academic employment. Based on a review of national studies and current literature, we recommend a shift from the current model, with its focus on dissertation research, to a broader conception of doctoral education that includes training and mentoring that will be relevant to future careers. We also highlight some of the national initiatives that have made progress in these areas. Doctoral education programs cannot remain static if they are to continue to create marketable graduates. Instead, partnerships should be formed with hiring institutions, so that doctoral programs can evolve in parallel with the dynamics of the job market.